2022
DOI: 10.1186/s13071-022-05329-0
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Aedes albopictus and Culex quinquefasciatus to Japanese encephalitis virus

Abstract: Background Japanese encephalitis virus (JEV) is the principal cause of mosquito-borne encephalitis in human populations within Asia. If introduced into new geographic areas, it could have further implications for public and animal health. However, potential mosquito vectors for virus transmission have not been fully investigated. The Asian tiger mosquito, Aedes albopictus, has emerged in Europe and is now expanding its geographical range into more northerly latitudes. Culex quinquefasciatus, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…On the other hand, it is interesting to note that models by Samy et al (2016) and Alaniz et al (2018) have identified temperate regions, including Ireland, as potentially suitable for Cx. quinquefasciatus ; findings that are supported by its detection in Turkey, which has European territory (Gunay et al 2015; Hernández-Triana et al 2022). In the USA, where Cx.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, it is interesting to note that models by Samy et al (2016) and Alaniz et al (2018) have identified temperate regions, including Ireland, as potentially suitable for Cx. quinquefasciatus ; findings that are supported by its detection in Turkey, which has European territory (Gunay et al 2015; Hernández-Triana et al 2022). In the USA, where Cx.…”
Section: Discussionmentioning
confidence: 81%
“…Mosquito infections were performed in the BSL-3 laboratory of the Zoonosis Science Centre in accordance with previous studies [ 23 , 46 48 ]. Female mosquitoes aged 7–14 days were deprived of sugar solution for 24 h before being presented with an infectious blood meal.…”
Section: Methodsmentioning
confidence: 99%
“…( Och .) dorsalis and Culiseta ( Culiseta ) annulata ) have shown potential as vectors in laboratory settings (Chapman et al., 2020; de Wispelaere et al., 2017; Hernandez‐Triana et al., 2022; Huber et al., 2014; Mackenzie‐Impoinvil et al., 2015). While Ae .…”
Section: Likelihood Of Transmission Of the Virus In The Eumentioning
confidence: 99%